Socialization of Child-Rearing Patterns with The Language of Love" in Rancamulya Village, Pameungpeuk District, Bandung Regency - Fiqhia Ratna Azhari; Delvi Marlia Sari; Devita Septiani Putri; Wasifah Hanim (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Parenting patterns for children are a determining factor in forming a child's character in adulthood. The quality and quantity of interactions between parents and children reflected Parenting patterns. This activity aims to provide counseling about parenting, focusing on parenting patterns for children in the language of love. The objects of the action were women from RW 10 Rancamulya Village. The methods used were participatory methods, lectures, and discussions. This parenting discussion on how to raise children using the language of love also discusses the stages of parenting children properly and how to build appropriate interactions with children. Implementing counseling on how to raise children by discussing love will provide a better understanding of how to educate children. Apart from that, it will also provide additional knowledge and improve skills for mothers in raising their children so that they will give birth to future generations with solid character and personality.